2017
DOI: 10.1007/s40122-017-0089-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Pain and Sleep: A Review

Abstract: Neuropathic pain is associated with sleep disturbances, and in turn poor sleep quality leads to increased pain sensitivity, so it is essential to assess sleep alongside neuropathic pain. Responses to drugs are inconsistent and identifying the best treatment option that will reduce pain and improve sleep quality remains challenging for clinicians. Anticonvulsants such as pregabalin and gabapentin improve neuropathic pain and have a positive effect on comorbid sleep disturbances. Opioids and antidepressants are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 32 publications
2
32
0
3
Order By: Relevance
“…We found that patients receiving TRZ reported favorable sleep outcomes (though this effect was similar across the three groups); our study, therefore, supports previous evidence showing that low doses of TRZ improve sleep. This effect might be particularly important in the clinical management of PDN, given the close association between neuropathic pain and sleep disturbances [26]. Trazodone, unique among antidepressants, has a mixed serotonergic and adrenolytic activity effective for multiple disorders including insomnia and anxiety [12,27].…”
Section: Discussionmentioning
confidence: 99%
“…We found that patients receiving TRZ reported favorable sleep outcomes (though this effect was similar across the three groups); our study, therefore, supports previous evidence showing that low doses of TRZ improve sleep. This effect might be particularly important in the clinical management of PDN, given the close association between neuropathic pain and sleep disturbances [26]. Trazodone, unique among antidepressants, has a mixed serotonergic and adrenolytic activity effective for multiple disorders including insomnia and anxiety [12,27].…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin has shown considerable efficacy for improved sleep interference as demonstrated by an improvement in sleep quality in 77% of patients [ 96 ]. Pregabalin and gabapentin are effective in treating neuropathic pain and have a positive effect on co-morbid sleep disturbance compared with opiates and antidepressants [ 97 ]. Sleep disturbance as well as its severity correlates with the severity of neuropathic pain and is a predictor of response to pregabalin in a post hoc analysis of placebo-controlled trials [ 98 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sleep disturbances decrease the quality of life and cause high health care costs and therefore, multimodal methods should be applied to improve the quality of life effectively. [33] Pregabalin is one of the most commonly prescribed analgesics for PHN. In many clinical studies, pregabalin used for PHN has been shown to reduce pain significantly, to improve sleep more compared to placebo, to have higher global efficacy, and to provide great improvement in patients with severe sleep disorders.…”
Section: Pain a Rimentioning
confidence: 99%